2009
DOI: 10.1016/j.appet.2009.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Vegetable bitterness is related to calcium content

Abstract: In the U.S. and Europe, most people do not consume the recommended amounts of either calcium or vegetables. We investigated whether there might be a connection; specifically, whether the taste of calcium in vegetables contributes to their bitterness and thus acceptability. We found a strong correlation between the calcium content of 24 vegetables, based on USDA Nutrient Database values, and bitterness, based on the average ratings of 35 people (r = 0.93). Correlations between the content of other nutrients and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 45 publications
0
23
0
Order By: Relevance
“…The occurrence and concentrations of alkaloids and glucosinolates vary according to species and cultivars as well as tissue type, physiological age and nutrition (Holst & Fenwick, 2003). A study by Tordoff and Sandell (2009) suggests that increased levels of calcium can also be responsible for the bitterness of vegetables. Although Amaranthus is a good source of calcium, no current study was conducted, indicating that the bitter taste of the leaves was related to the calcium content.…”
Section: 2mentioning
confidence: 99%
“…The occurrence and concentrations of alkaloids and glucosinolates vary according to species and cultivars as well as tissue type, physiological age and nutrition (Holst & Fenwick, 2003). A study by Tordoff and Sandell (2009) suggests that increased levels of calcium can also be responsible for the bitterness of vegetables. Although Amaranthus is a good source of calcium, no current study was conducted, indicating that the bitter taste of the leaves was related to the calcium content.…”
Section: 2mentioning
confidence: 99%
“…Panellists were asked if any individual leaf was found to be particularly undesirable and in this case 16 of the 26 panellists (61.5%) found the Radicchio leaf to be undesirable within the salad mix. The Radicchio leaf is understood to be a spicier and a more bitter intense leaf [ 25 ] which most panellists found undesirable when compared to the Red Batavia alternative. Both salad Mixes 1 and 2 had no significantly positive or negative attributes associated when compared with each other.…”
Section: Resultsmentioning
confidence: 99%
“…In Europe and USA, collard greens are available year-round, but it may taste better when harvested in early spring or after Frost, which is less bitter, and it has been extensively used in the people meal in the region [5]. However, this kind of vegetable has not been grown in China, maybe due to it is rough texture and the bitter taste, no study on its nutrients have been reported from the China produce.…”
Section: Collard Greenmentioning
confidence: 99%